ANALISIS PENYIMPANGAN TUGAS DAN FUNGSI PUBLIC RELATIONS DALAM MEMBENTUK CITRA PERUSAHAAN - Angga Intueri Mahendra Purbakusuma (Universitas Teuku Umar, 2018)
Practice of Public Relations have recently tended to blur the original concept launched by Public Relations founders. Even though a practice of a Public Relations take a crucial role in run management functions so that the relationship between the companies concerned with the public can be harmoniously intertwined. Hence, the purpose of this research is to determining how the form of deviations from duties and functions of Public Relations in build corporate image. The research was conducted using a qualitative approach with descriptive methods, descriptive analysis which describes the role of Operational Secretary (OPS) as Public Relations in enhancing the corporate image for a supplier company engaged in construction services business in Batam and the data analysis techniques used by investigators are components of the data analysis by Miles and Huberman Interactive Model. The results of this research indicate that the implementation of the duties and functions of Public Relations as an effort to build corporate image. Implementation of Public Relations activities can not be said optimal because does not have a special section in handling the tasks and functions of Public Relations, but delegate tasks and functions of Public Relations is the Operational Secretary (OPS). The absence of a separate section of Public Relations, limited resources that can be used, and other administrative work that must be done by Operational Secretary (OPS) which takes time and focus is the obstacle faced by Operational Secretary (OPS) in performing duties and functions as Public Relations. The conclusion of this research shows that public relations is a very important to role in build a corporate image. Public Relations role maintaining good communication and relationship with internal and external public companies, to increase the company's existence. With emphasis on quality of service for consumers, establish good relationships with various public companies and tried to give a good impression in the community. So thus a positive corporate image will be formed in accordance with the expectations of the company. Keywords: Deviations, Public Relations, Corporate Image